Pandemic policies and breastfeeding: A cross-sectional study during the onset of COVID-19 in the United States - Palmquist, Aunchalee E. L.; Tomori, Cecília; Tumlinson, Katherine; Fox, Carolyn; Chung, Stephanie; Quinn, E. A. (Frontiers in Sociology, 2022)
The United States is one of the few countries, and the only high-income country, that does not federally mandate protection of postpartum employment through paid postpartum maternity and family leave policies. At the onset of the COVID-19 pandemic in the U.S., stay-at-home orders were implemented nationally, creating a natural experiment in which to document the effects of de facto paid leave on infant feeding practices in the first postpartum year. The purpose of this cross-sectional, mixed-methods study was to describe infant and young child feeding intentions, practices, decision-making, and experiences during the first wave of the COVID-19 pandemic in the U.S. Quantitative and qualitative data were collected March 27–May 31, 2020 via online survey among a convenience sample of respondents, ages 18 years and older, who were currently feeding a child 2 years of age or younger, yielding 1,437 eligible responses. Nearly all (97%) respondents indicated an intention to feed their infant exclusively with human milk in the first 6 months. A majority of respondents who were breastfeeding (66%) reported no change in breastfeeding frequency after the implementation of COVID-19 stay-at-home orders. However, thirty-one percent indicated that they breastfed more frequently due to stay-at-home orders and delayed plans to wean their infant or young child. Key themes drawn from the qualitative data were: emerging knowledge and perceptions of the relationship between COVID-19 and breastfeeding, perceptions of immune factors in human milk, and the social construction of COVID-19 and infant and young child feeding perceptions and knowledge. There were immediate positive effects of stay-at-home policies on human milk feeding practices, even during a time of considerable uncertainty about the safety of breastfeeding and the transmissibility of SARS-CoV-2 via human milk, constrained access to health care services and COVID-19 testing, and no effective COVID-19 vaccines. Federally mandated paid postpartum and family leave are essential to achieving more equitable lactation outcomes.